The Effect of the Use of Quizizz-Assisted Learning Media on the Learning Interest of Elementary School Students - Ardita, Rona Syafira; Alzaber, Alzaber; Rezeki, Sri; Wahyuni, Astri (AlphaMath : Journal of Mathematics Education, 2024)
The purpose of this study is to determine whether Quiziz media has an impact on sixth-grade elementary school pupils' interest in learning. This study uses an experimental pretest-posttest one-group design. The population in this research consists of all sixth-grade students at SD Kartika 1-9 Pekanbaru, totalling 21 students. The sampling technique is saturation sampling, where the entire population is used as the sample. An interest questionnaire with 20 questions determines students' learning interests. Descriptive and inferential statistical analysis are the methods of data analysis that are employed. According to the findings of the descriptive study, the average score on the pretests was 58.19 before the use of Quizizz-assisted media (pretest) and had risen to 66.05. In the meantime, a Sig(2-tailed) value of 0.002 was derived based on the results of inferential analysis, where the value was less than 0.05 (0.002 < 0.05). Consequently, it might be said that "Hypothesis Accepted" or that H0 is rejected and H1 is accepted. Therefore, it may be concluded that a factor influences the rise in learning interest among sixth-grade elementary school pupils.